EVALUASI PELAKSANAAN PUBLIK SAFETY CENTER (PSC) 119 DINAS KESEHATAN PROVINSI RIAU TAHUN 2025 - Lismardani; Hartono, Budi; Anusirwan (LPPM Universitas Awal Bros, 2025)
The Public Safety Center (PSC) 119 of the Riau Provincial Health Office is a key component of the Integrated Emergency Management System (SPGDT). This study aims to evaluate the effectiveness of PSC 119 implementation in 2025 and to identify supporting factors, barriers, and required strengthening prior to the planned transition toward establishing district–city PSC units in 2026. A qualitative approach was employed through interviews, observations, document reviews, and the problem-solving cycle, including situation analysis, priority setting using the USG method, and root cause analysis using a fishbone diagram. Findings indicate that PSC 119 received 271 calls from January to June 2025, predominantly non-emergency cases. Limited human resources, insufficient funding, inadequate infrastructure, and incomplete standard operating procedures were identified as major challenges to effective service delivery. Cross-sector coordination and public awareness were also suboptimal. The study concludes that PSC 119 requires institutional strengthening, improved workforce capacity, digitalization of operational systems, and sustained financial support to ensure a more responsive and integrated emergency service. These evaluation results provide essential input for future policy direction in developing district-level PSC units across Riau Province.